2021
DOI: 10.1002/mp.14821
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Practical implementation strategies of cycloidal computed tomography

Abstract: Purpose: Cycloidal computed tomography is a novel imaging concept which combines a highly structured x-ray beam, offset lateral under-sampling, and mathematical data recovery to obtain highresolution images efficiently and flexibly, even with relatively large source focal spots and detector pixels. The method reduces scanning time and, potentially, delivered dose compared to other sampling schemes. This study aims to present and discuss several implementation strategies for cycloidal computed tomography (CT) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…In step-and-shoot scans, the repeated stop-starting of the rotation and translation motors can lead to significant overheads. On the contrary, cycloidal acquisitions can be realized as flyscans 27 , where the sample is simultaneously rotated and translated without interruption. Provided that the detector integration time is negligible, overheads are removed and scan time is equal to exposure time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In step-and-shoot scans, the repeated stop-starting of the rotation and translation motors can lead to significant overheads. On the contrary, cycloidal acquisitions can be realized as flyscans 27 , where the sample is simultaneously rotated and translated without interruption. Provided that the detector integration time is negligible, overheads are removed and scan time is equal to exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that an even coverage of the sinogram, as can be seen in panel (c), provides a favourable configuration for recovering the missing data using mathematical methods 6 . Simulations and experimental results suggest that cycloidal CT can yield a resolution comparable to dithering without having to apply time-consuming step-scanning of the sample at each rotational position 27 .…”
Section: Cycloidal Computed Tomographymentioning
confidence: 98%
See 2 more Smart Citations
“…effectively sampled at a frequency higher than the pixel pitch) MTF 31,32 . The A c c e p t e d M a n u s c r i p t 6 relevance of this work goes beyond EI XPCI and is more generally applicable to methods using pre-sample masks, either to gain access to some degree of phase-based image contrast or specifically to increase the resolution [33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%